Re-creating the circle : the renewal of American Indian self-determination - Harris, LaDonna; Sachs, Stephen M., 1938-; Morris, Barbara, 1959- (University of New Mexico Press, 2011)
A collaboration between Native activists, professionals, and scholars, Re-Creating the Circle brings a new perspective to the American Indian struggle for self-determination.